2011
DOI: 10.1590/s1678-77572011000300019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reduced exposure times on the cytotoxicity of resin luting cements cured by high-power led

Abstract: ObjectiveApplications of resin luting agents and high-power light-emitting diodes (LED) light-curing units (LCUs) have increased considerably over the last few years. However, it is not clear whether the effect of reduced exposure time on cytotoxicity of such products have adequate biocompatibility to meet clinical success. This study aimed at assessing the effect of reduced curing time of five resin luting cements (RLCs) polymerized by high-power LED curing unit on the viability of a cell of L-929 fibroblast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 24 publications
1
26
2
2
Order By: Relevance
“…Gupta and collaborators reported that the MTT test is the most widely used method for measuring cytotoxicity of composite resins. Succinic dehydrogenase and alkaline phosphatase responses have also been used for the same purpose 39 . However, the fate cells cannot be followed up, since the MTT assay requires killing the cells at each measurement time point.…”
Section: Discussionmentioning
confidence: 99%
“…Gupta and collaborators reported that the MTT test is the most widely used method for measuring cytotoxicity of composite resins. Succinic dehydrogenase and alkaline phosphatase responses have also been used for the same purpose 39 . However, the fate cells cannot be followed up, since the MTT assay requires killing the cells at each measurement time point.…”
Section: Discussionmentioning
confidence: 99%
“…2 Furthermore, when used for cementing ceramic systems, resin cements increase the fracture strength and stability and show excellent esthetic results. 3,4 However, when this material is inadequately polymerized, clinical problems may arise, such as inadequate biocompatibility, 5 microleakage and recurrent caries, 6 susceptibility to degradation, marginal ditching, 7 discoloration, and reduction of mechanical properties. 8 Therefore, the clinical success, longevity, and biocompatibility of indirect restorations are largely dependent on an appropriate degree of conversion of the resin cement.…”
Section: Introductionmentioning
confidence: 99%
“…We, in this study, have tried to create a homogeneous environment to evaluate the film thickness of three commonly used materials. Since this is an in vitro study, other influencing factors, such as intrapulpal temperature, 15 humidity, water/powder ratio, and type of preparation 16 are not taken into consideration, which depicts limitations of the present study. Jorgensen and Petersen 17 reported significant reductions in film thickness when a tapered pin system was substituted for the method described in the ADA specification no.…”
Section: After the Introduction Of Gic In 1972mentioning
confidence: 99%